Tolerance of Public Open Space Utilization of Urban Kampung in Surakarta City - Rayi Anindya Pitoka Pramono; Dwita Hadi Rahmi (Built Environment Studies, 2021)
This paper aims to determine the form, type, and utilization of public open space in the urban kampung and see the extent of tolerance in it. Limited land does not make the urban kampung stop providing public open space for its citizens. For this reason, three samples of urban villages were chosen that are considered to represent the characteristics of urban kampungs in the city of Surakarta. The three kampungs are Pringgolayan Village which is the center of several home industries, Karengan Village is a village on the banks of the Solo River, and Mloyokusuman Village is a traditional kampung within Beteng Keraton. This research was conducted by direct observation and interviews with key informants. The results obtained from this study are that there are various types, forms, and uses of public open space in urban villages. As well as the high level of tolerance in the use of public open space in urban kampung so that although there is limited land, conflict tends to be minimal.